Tak1 in the astrocytes of mediobasal hypothalamus regulates anxiety‐like behavior in mice. Issue 3 (26th September 2020) - Zhao, Faming; Zhang, Tingting; Shen, Qing; Yin, Kaili; Wang, Yu; Zhang, Guo
Abstract: Anxiety disorder is characterized by excessive fear, anxiety, and avoidance of perceived threats in internal to oneself or the environment, however, the underlying mechanisms are less well understood. Here, we show that transforming growth factor‐β‐activated kinase 1 (Tak1) expressed in the astrocytes of mediobasal hypothalamus (MBH) plays a crucial role in anxiety‐like behavior in mice. Our data demonstrate that deficiency of Tak1 in astrocytes increased anxiety level, but did not impact locomotor activity in mice. Astrocytic activation of Tak1 in the MBH mitigated the anxiety‐like behavior, whereas suppression of Tak1 in MBH astrocytes promoted the anxiety‐like behavior in mice. Collectively, these data suggest that Tak1 expressed in the MBH astrocytes could modulate the anxiety‐like behavior in mice. Main Points: Deficiency of Tak1 in astrocytes facilitates anxiety‐like behavior. Activation of Tak1 in the MBH astrocytes is anxiolytic. Suppression of Tak1 in the MBH astrocytes is anxiogenic.